1994
DOI: 10.1002/1520-6807(199407)31:3<188::aid-pits2310310303>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the diagnosis of attention deficit/hyperactivity disorders meaningful?

Abstract: This research examines 75 children, previously diagnosed with attention deficit/ hyperactivity disorders (AD/HD), referred to a multidisciplinary medical setting because of unsatisfactory response to medical or educational interventions. Systematic descriptive data from parents and teachers have been compared with the 14 symptoms characterizing the AD/HD syndrome in the DSM-III-R (APA, 1987). The initial reasons for referral have been reexamined using an extended list of diagnostic descriptors, and nearly one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…none at all (Cotugno, 1993;Desgranges, Desgranges, & Karsky, 1995;Sabatino & Vance, 1994). For instance, Cotugno (1993) found that only 22% of children referred to a specialized ADHD clinic were given a primary diagnosis of ADHD, and only 37% of the referrals were given a secondary diagnosis of ADHD.…”
mentioning
confidence: 99%
“…none at all (Cotugno, 1993;Desgranges, Desgranges, & Karsky, 1995;Sabatino & Vance, 1994). For instance, Cotugno (1993) found that only 22% of children referred to a specialized ADHD clinic were given a primary diagnosis of ADHD, and only 37% of the referrals were given a secondary diagnosis of ADHD.…”
mentioning
confidence: 99%
“…Furthermore, many of the char acteristics of gifted, learning-disabled students and gifted underachievers (see, for example, Baum, 1989;Clark, 1997) strongly resemble those used in checklists to determine the presence of an Attention Deficit Disorder. Sabatino and Vance (1994) noted that 8 of the 14 characteristics used to determine Attention Deficit/ Hyperactivity Disorder were so similar to characteristics of learning disabilities and other academic and behavioral problems that they Author Notes 1. All names of people (other than the authors) are pseudonyms.…”
Section: Contributing Factors At Homementioning
confidence: 99%
“…Los profesores/as son una de las fuentes más importantes de información crítica con respecto a la categoría diagnóstica de TDAH, ya que, al permanecer en contacto directo diariamente con el alumnado, suelen ser de los primeros en detectar dicho trastorno [31,32].…”
Section: Introductionunclassified